Implementação de um serviço de telemetria do OpenStack em um ambiente Cloud Computing - Soares, Jackson (2015)
Since the beginning of the decade, Cloud Computing have ceased to be a concept and came to be a new paradigm, influencing the making of decisions for large companies around the world and affecting directly and indirectly many people. The objective of this work is to develop a telemetry service for calculating estimates and creating resource usage reports in a OpenStack cloud. This work will about Cloud Computing, exposing it's concepts, features, and it's influences among the Information Technology. As Cloud Computing advances, so advances our efforts, investments and projects all over the place. OpenStack is an example of stable open source platform for the cloud. Providing a range of options and opportunities to develop applications based on their services. Against this scenary, came the need of developing one application with objective to estimate the resource usage provided by the cloud. Therefore, the deployment and use of a Telemetry service and it's methods was conducted. For the development of this work, and of the resulting application, was made choosing the topic, bibliographic and technical studies, system implementation, collection and analysis of results. It was concluded the results as positive and satisfactory, since tests have shown that the developed application provides control and management of the use of resources in the cloud, providing transparency for all types of users, and this work can be used for the community in general, for further studies taking into account computational clouds and similar studies problems.